A Prospective Multicenter Clinical Performance Evaluation of the C-CGM System - Rebec, Mihailo; Cai, Kevin; Dutt-Ballerstadt, Ralph; Anderson, Ellen (Journal of diabetes science and technology, 2022)
Continuous glucose monitors (CGMs) have had a significant impact on the management of diabetes mellitus. We present the results of a multinational evaluation of the Cascade CGM ("C-CGM") over 14 days of in-clinic and home use. Each of the 57 enrolled type 1 diabetes mellitus and type 2 diabetes mellitus subjects wore 2 C-CGMs on the abdomen for 14 days. One part of the evaluation was the performance versus reference glucose values generated for 12 -hour in-clinic sessions on days 1, 4, 7, 10, and 14. Glucose blood samples were drawn every 15 minutes and analyzed with the Yellow Spring Instruments (YSI) 2300 glucose analyzer. The performance assessment on in-clinic days was based on paired YSI/CGM data points and on home-use days was based on paired fingerstick BGM (blood glucose monitoring)/CGM data points. A total of 17 823 CGM/YSI data points during in-clinic use was analyzed. The mean absolute relative difference for glucose values between 100 and 400 mg/dL (MARD) and mean absolute difference for values between 40 and 100 mg/dL (MAD) were 11.5% and 15.1 mg/dL, respectively. The system accuracy during home use was 12.7% and 15 mg/dL for MARD and MAD, respectively. There were no serious adverse events or infectious complications reported. A modified algorithm "Hybrid Algorithm" was used in a prospective analysis of the in-clinic data, resulting in a MARD of 9.9% and MAD of 14.5 mg/dL. The performance of the C-CGM device over 14 days meets the safety and efficacy standards of CGM systems for managing blood glucose levels in people with diabetes. This was further confirmed when the C-CGM system was given approval for CE Mark in October 2019.